ANALISIS PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP MATA PELAJARAN GAMBAR TEKNIK - Sigit Ari Wibowo (CV. ADIBA AISHA AMIRA, 2024)
Learning technical drawing is very important to develop students' understanding of basic engineering design concepts, such as 2D and 3D modeling. Students must understand these concepts well beyond just learning theory; they must also be able to use their knowledge in real situations. PjBL emerged as a learning method that can integrate theory with practice to provide students with a broad and challenging learning experience. This research will explore the role of PjBL in improving student learning outcomes regarding technical drawing. By analyzing various international and national accredited journals, this research will evaluate how well PjBL improves students' understanding of technical drawing concepts and their ability to apply these concepts in the real world.